KEMAMPUAN LITERASI PROSA ANAK PADA TINGKAT SEKOLAH DASAR - Nazwa Dwi Syafiti; Usiono Usiono (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The purpose of this study is to discuss children's prose literacy skills at the primary school level. This research aims to explore the importance of scientific work in the context of higher education through the systematic literature review method. This research method uses the literature study method.b Data collection is done by finding sources and constructing from various sources such as books, journals and research studies that have been done. The results showed that grade 3 students' prose literacy skills were still below the adequacy standard, with an average score of 61 for reading analysis and 47 for prose writing. This finding indicates the need for more attention in literacy development among children, especially in the context of distance learning. This study is expected to provide insights for educators and policy makers to improve literacy programs in primary schools.